Root resorption and pulpal changes due to intrusive force. - (:unkn) unknown (My University, 1994)
Intrusion has been regarded as a controversial topic in the literature. It is apparent from many studies that excessive forces applied in orthodontic treatment might lead to undesirable results such as circulatory disturbances, pulp degeneration, calcification and even necrosis. This study was performed to observe the reaction of pulp and roots following tooth intrusion. Material consisted of four first premolar teeth of two adult patients. One premolar of each patient was intruded orthodontically and the other premolars were taken as controls. The palatal roots of the experimental teeth were cut and examined in scanning electron microscope (SEM) and the pulps of the teeth were examined in transmission electron microscope (TEM). At SEM examination, root surfaces of intruded teeth showed resorption cavities of different diameters and depths. At TEM examination, vascular degeneration was the main change in the pulps of experimental teeth.